Capital adequacy in insurance sector - Birkent, Eda (My University, 2002)
Ö Z E T SİGORTA SEKTÖRÜNDE SERMAYE YETERLİLİĞİ Bu tez çalışmasının amacı Türkiye ve dünyada sigorta şirketlerinin sermaye yeterliliğini inceleyip, sigorta sektöründe uluslararası bir sorun haline gelmiş bu konu hakkında hem sigorta ettirenlerin hem de sigorta şirketlerinin haklarını gözeterek sermaye yeterliliğini incelemektir. Bir sigorta şirketinin mali yeterlilik içinde bulunması, (hasarlarını ve giderlerini) ödeyebilecek durumda olması anlamına gelir. Sigorta ve/ veya reasürans şirketinin mali açıdan yetersiz olması hali, hasarların ödenebilmesi için gerekli aktiflerinin yetersiz (borca batık) veya zamanında paraya çevrilemez (likidite eksikliği) durumda olmasının sonucudur. Başka bir tanımlamayla sigorta şirketinin mali gücü veya yeterliliği, yüklenimlerini karşılayabilecek ölçüde teknik karşılıklarının ve yeterli sermaye güvencesinin bulunup bulunmadığına bağlıdır. Bir sigorta şirketinin mali yeterlilik marjı (seviyesi) sermaye yapısı veya tabanını belirler. Şirket aktiflerinin, pasifleri aşması halini ve aşan kısmını tanımlar. Aşan kısma İngilizler genellikle ortakların, Amerikalılar ise sigortalıların aşkın fonları derler (Shareholders fund's- Policyholders surplus). Mali yeterlilik oranı (rasyosu), yeterlilik marjının prim üretimine oranını verir. Sigorta işletmelerinde mali yeterlilik marjının ayrı bir önemi vardır. Zira imalat işletmelerinden farklı olarak sigorta işletmelerinde sermayenin işlevi, finansmandan çok garanti ve güvencedir. Bu bağlamda mali yeterlilik marjı, sigorta işletmelerinde yıl içindeki ve yıllar arasındaki dalgalanmaları stabilize eden, dolayısı ile mali çöküntüyü önleyen bir yastık vazifesi görür. Tez yedi bölümden oluşmaktadır. İlk bölümde geniş bir kaynak taraması yapılarak mali yeterlilik ve sermaye yeterliliği teknikleri üzerine araştırmalar, daha sonraki bölümlerde de Türkiye ve dünyada bu tekniklerin kullanımı, sonuçları ve sektördeki geleceğe yönelik beklentiler üzerinde durulmuştur. Amaç olarak bu çalışma rekabetin çok fazla olduğu sigorta sektöründe sigorta şirketlerinin finansal yapılarını güçlendirmeleri için gerekli olan sermayenin yeterliliği ve yapılması gereken iç ve dış denetimler üzerinde durulmuş, risk, mali yeterlilik ve sermaye maliyeti arasındaki ilişkiler üzerine araştırmalar yapılmıştır.

CAPITAL ADEQUACY IN INSURANCE SECTOR Objective of this study is to analyse the adequacy of insurance companies, which is an international problem of the insurance sector worldwide, from the risk point of view. The reason is that the capital is the most valuable and important resource that has been used by the shareholders, creditors and policyholders as a cushion against financial and insurance risks insurance companies face in the sector. In recent years a company's financial security is becoming increasingly important in the insurance industry. This trend towards deregulation and globalisation in the insurance and the financial markets is leading to keener competition and to greater price fluctuations. Capital adequacy requirement methods reduce the probability of future insolvency of an insurance company to some predetermined minimum level or alternatively reduce the number of insurance companies that fail to present sufficient guarantee in order to cover the rights of policyholders and other creditors. This study is composed of seven parts. In order to evaluate the capital adequacy of insurance companies the thesis includes an extensive literature survey about solvency and capital adequacy techniques in the world. The current situation of Turkish insurance sector and future expectations, essential terms in insurance and reinsurance,the typical risks and their prevention techniques in insurance sector that insurance companies face all over the world, solvency requirements of insurance companies, the regulatory approaches in solvency control and methods used to rate solvencies in EU, in US and in Turkey and their comparison, a case study to analyse the solvency of an insurance company ,capital and capital adequacy which are important tools in insurance supervision are underlined in the first five parts of this study. The findings indicates that there is, in general, a high level of success among insurance companies in the world to achieve the minimum required capital, and mostly in the countries where state regulations are effective there is very little number of insurance companies that face insolvencies with the cause of an inadequate capital. In the sixth and the last part of the thesis, the capital requirement ratings of rating agencies such as the best known rating agencies in the world Standard&Poor's,(S&P), Moody's and specialising exclusively in insurers A.M.Best are evaluated to see the capital adequacy of insurance companies in the financial markets. This study shows that, high competition and everday changing needs and demands of policyholders force insurance companies to have a strenghter financial position in the market. In this respect determining the necessary capital is a very important point for the insurance companies. The assessment of an insurers' solvency by supervisory authorities, rating agencies, brokers, cedants etc. centers on the adeqaucy of the insurer's capital funds. In order to stay competitive, companies need to have true capital costs and adequate capital. In this thesis an analysis is made to show the trade off between security and capital costs that has a great importance in determining the adequacy of capital of an insurance company.
Keywords: Sigorta; Sigorta Ve Sigortacılık